Pengukuran Koefisien Serapan Bunyi Spons dan Styrofoam dengan Menggunakan Smartphone - Sandi Sandi; Kumalasari Kumalasari; Jefri Akbar; Rospita Sari; Fitri Afriani (Jurnal Riset Fisika Indonesia, 2020)
In this study, we analyzed the characteristics of samples sound absorption coefficient from sponge and styrofoam using a smartphone. The sound absorption coefficient is measured using a sound level meter and a frequency generator installed on a smartphone to determine the sound absorption coefficient. Samples were formed in circles with different thickness variations ranging from 1.5 cm to 15 cm. Through the tests that have been done, it can be seen that styrofoam has a higher sound absorption coefficient value than sponges. This research provides an alternative solution for measuring the sound absorption coefficient based on a smartphone device so that it is easy to apply, primarily to support the learning process related to sound material.